Solve for x 9-2x=-1

Math
9-2x=-1
Move all terms not containing x to the right side of the equation.
Tap for more steps…
Subtract 9 from both sides of the equation.
-2x=-1-9
Subtract 9 from -1.
-2x=-10
-2x=-10
Divide each term by -2 and simplify.
Tap for more steps…
Divide each term in -2x=-10 by -2.
-2x-2=-10-2
Cancel the common factor of -2.
Tap for more steps…
Cancel the common factor.
-2x-2=-10-2
Divide x by 1.
x=-10-2
x=-10-2
Divide -10 by -2.
x=5
x=5
Solve for x 9-2x=-1

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top